A CLINICAL COMPARATIVE EVALUATION OF EFFICACY AND SAFETY OF KUMARYASAVA AND RAJAHPRAVARTANI VATI IN THE MANAGEMENT OF PRATHMIK KASTARTAVA W.S.R. TO (PRIMARY DYSMENORRHOEA): A PROSPECTIVE OPEN LABEL SINGLE CENTER STUDY - Lal, *Pravesh Tomar; Lal, Sudeep Kumar; Garg, Saloni (International Journal of Ayurveda and Pharma Research, 2017)
Background: Primary dysmenorrhoea is most prevailing symptom in young adolescent girls. It can start before menarche and may be present continuously for years even after the patient get married and have children. Kashtartava can be expressed as- â€œkashten munchyati iti kastartavaâ€ i.e. the condition where Artava is shaded with great difficulty and pain is termed as â€œKashtaravaâ€. Kashtartava is mentioned as a specific symptom in Vatala, Paripluta, Udavartini Yonivyapad, Vataja Artava Dusti, Kshina Artava-Dusti And Asrigdar and the diseases in which whole symptomatology denotes Kashtartava, are Pittala, Sannipataki, Suchimukhi Yonivyapada and Artavakshaya. Aims and objectives: To compare and evaluate the efficacy and safety of Kumaryasava with Rajahpravartani Vati in the patients suffering from Prathmik- Kashtartava. Material and methods: A prospective open label study was carried out at OPD of Prasuti â€“Tantra and Stri Roga department. 76 patients satisfying the selection criteria were enrolled, however data of fifty patients was used for analysis and comparative study. 50 patents were divided into two groups (A and B) with twenty five patients in each. Patients of group A were administered Kumaryasava 20 ml with equal amount of water and that of group B were administered tab Rajahpravartini vati (125 mg) 2BD after meal with normal water before 7 days of menses and during menstrual cycle. Total duration of course of medicine was 3 consecutive cycles. Follow-up was done at every menstrual cycle during the treatment and follow- up without treatment was done for next three cycles. Assessment of intensity of pain was done by VAS and VMSS according to the memory and presentation of the patient. The pain was assessed at baseline and at every menstrual cycle. Results: After three month of treatment, in both groups the baseline pain was found to be improved in every cycle But when the overall result was observed highly significant results were found in group B in comparison to group A. The effect of Kumaryasava on associated symptoms was found to be more than Rajahpravartini vati. Conclusion: Kumaryasava and Rajahpravartani Vati administered in cases of dysmenorrhea in above mentioned doses were found safe and effective in pain but Rajahapravartini Vati showed more effect on overall symptoms of dysmenorrhea including pain and menstrual pattern though Kumaryasava was found to be more effective in associated sign and symptoms of dysmenorrhea.